2008
DOI: 10.1007/s10616-008-9121-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of gingerol on the proliferation and invasion of hepatoma cells in culture

Abstract: Effect of [6]-gingerol, a major pungent component in ginger, on the proliferation of a rat ascites hepatoma AH109A cells was investigated by measuring [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Such a benefit has also been observed with febuxostat in left ventricular hypertrophy in mice [25] and congestive heart failure in dogs [26]; wherein febuxostat has restored myocardial functions. This beneficial effect can be explained by inhibition of xanthine oxidase by febuxostat with a resultant decrease in free radical production and inhibition of apoptosis, consistent with the effects previously reported with other xanthine oxidase inhibitors such as allopurinol [10] and 6-gingerol [27].…”
Section: Discussionsupporting
confidence: 88%
“…Such a benefit has also been observed with febuxostat in left ventricular hypertrophy in mice [25] and congestive heart failure in dogs [26]; wherein febuxostat has restored myocardial functions. This beneficial effect can be explained by inhibition of xanthine oxidase by febuxostat with a resultant decrease in free radical production and inhibition of apoptosis, consistent with the effects previously reported with other xanthine oxidase inhibitors such as allopurinol [10] and 6-gingerol [27].…”
Section: Discussionsupporting
confidence: 88%
“…These firmly suggest that [6]-gingerol can effectively be used for the treatment of gastric cancer (Ishiguro et al, 2007). Yagihashi et al (2008) reported that [6]-gingerol inhibited both proliferation and invasion of hepatoma cells in a dosedependent manner at concentrations of 6.25-200 muM (proliferation) and 50-200 muM (invasion). Suppression of hepatoma cell proliferation by [6]-gingerol may be due to cell cycle arrest and apoptosis induction.…”
Section: Cancer Insurgence and Gingermentioning
confidence: 86%
“…It was demonstrated that 6-, 8-, and 10-gingerols and 6-shogaol showed efficacy in anti-inflammatory, antibacterial, antipyretic, antilipidemic, antitumorigenic, and antiangiogenic effects (5,(21)(22)(23)(24)(25)(26)(27). In addition, 6-gingerol was shown to inhibit leukotriene A 4 hydrolase (LTA 4 H) and suppress anchorage-independent cancer cell growth in colorectal cancer cells (HCT116 and HT29) with IC 50 's of 50 and 35 μM, respectively (28).…”
Section: Introductionmentioning
confidence: 99%